Green Hydrogen and Formula 1: Advancing Sustainable Comprehensive Approaches for F1 Racing in the MENA Region - Fekri, Feryal (Journal of Sustainable Development Law and Policy, 2025)
Formula 1 (F1) has embarked on sustainability initiatives, notably the ’Countdown to Zero’ campaign aimed at achieving carbon neutrality by 2030. This article delves into F1’s sustainability efforts, focusing on the integration of green hydrogen as a promising solution for reducing carbon emissions, particularly within the Middle East and North Africa (MENA) region. Despite the novelty of green hydrogen in F1, its potential applications in powering vehicles and supporting event logistics are explored. Additionally, the article examines MENA’s significance in F1’s sustainability agenda, given its abundant renewable energy resources and strategic position in hosting Grand Prix races. The feasibility of transitioning F1 cars to sustainable alternatives, including electric vehicles, hydrogen-powered cars, and e-fuels, is scrutinized, highlighting challenges and opportunities. Furthermore, the article discusses sustainable practices that can make F1 events more sustainable. It refers to sustainable practices previously implemented in past F1 Grand Prix races, assesses their applicability to the MENA region, and suggests innovative practices that the MENA can implement; these include the installation of solar canopies in F1 circuit parking lots and the use of bio-fuelled trucks for event logistics. Investment in sustainable aviation fuel (SAF) emerges as another avenue for F1 to mitigate its carbon footprint, potentially through partnerships with airlines present in the MENA region, such as Emirates. Ultimately, this article underscores the imperative for F1 to embrace sustainable practices, not only to align with societal trends but also to lead the charge in environmental stewardship within the realm of motorsport.